2013
DOI: 10.1016/j.pedneo.2012.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Length of Stay in the Pediatric Emergency Department

Abstract: Patients who were waiting for hospitalization for less than 8 hours or were not admitted, those without any laboratory tests, those having door-to-physician time less than 60 minutes, and those without any gastrointestinal symptoms had the shortest LOS. Patients who waited for hospitalization for more than 16 hours had the longest LOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
1
8
0
1
Order By: Relevance
“…The risk factors that we studied may be different from what was considered by previous studies from other regions because of differences in organisation of health systems. For example, Wiler et al32 in USA, studied the impact of ambulance diversion on hospital stay which was not considered by us while in a paediatric ED, Li et al33 found that delayed hospitalization greater than 16 hours had the longest LOS.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The risk factors that we studied may be different from what was considered by previous studies from other regions because of differences in organisation of health systems. For example, Wiler et al32 in USA, studied the impact of ambulance diversion on hospital stay which was not considered by us while in a paediatric ED, Li et al33 found that delayed hospitalization greater than 16 hours had the longest LOS.…”
Section: Discussionmentioning
confidence: 96%
“…Although pattern of presentations and predictors of paediatric hospital stay has been reported in the high income countries3033, little is known currently in our environment.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the covariates, such as consultations, laboratory tests, CT exams, and radiographs have previously been mentioned [14, 15, 25, 26]. Despite the fact that more exams indicate longer ED LOS, the magnitude of the impact of these exams and services has rarely been quantified and compared.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, patients' length of stay in the ED has been a concern due to its impact on patient safety and satisfaction (4). Each patient's LOS is measured from the patient's initial arrival to the transfer to the other department, and it is used as a key to assessing the efficiency of improving management and clinical performance (5).…”
Section: Introductionmentioning
confidence: 99%